Globalization and politics : promises and dangers - Lane, Jan-Erik. (Hampshire, 2006)
"Globalization and Politics" brings together vision and imaginative insight to the analysis of the evolution of inter-state politics to produce a clear, comprehensive and coherent sense of how globalization works and how it might work better. The study looks upon globalization as a distinct set of phenomena - energy, economy, environment and politics - all of which interact. Presenting opportunities for interdependency and governance, globalization offers both dangers and promises which explains why it is equally feared and praised. Globalization is an economic trend with strong spillovers and as such has become a political trend with cultural implications. This volume is an invaluable, highly readable new text for graduate and undergraduate courses. It sets out the key challenges for globalization in the 21st century and looks at the challenges, responses and risks of globalization. It is required reading for analysts, students and professionals who want to understand what's at stake in the globalization debate.
Keywords: Globalization